Análisis de flujo de pasajeros en el sistema de transportación público en la vía Loja Catamayo Caso de estudio Cooperativa Catamayo - Alvarado Orellana, Paola Gabriela (2018)
Abstract:The need for mobilization of people, current traffic problems and pollution, generated increased demand for public transport, which it operates through frequencies, routes and tariffs set. In Ecuador there are different modes of public transport, among them the intraprovincial transportation, National Transit Agency (ANT) is the regulator of this type of transport, but this entity has little information it difficult to improve the quality of transportation service, against this, the present study aims to determine the variation in the flow of passengers in the Loja Catamayo road, with reference users Catamayo Cooperative. To obtain information studies were conducted: ascent and descent passenger, punctual demand and timely travel times and delays, this information allowed to elaborate graphs hourly and daily flow; hourly, daily, weekly and monthly passenger demand; also travel speeds and running of vehicle units Catamayo Cooperative obtained. Finally, according to the results analysis it was determined information that will serve for planning, organization and control service offered by the cooperative.